2014
DOI: 10.1002/ange.201400927
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Secondary Structure Mimic Based On Piperidine‐piperidinones

Abstract: Minimalist secondary structure mimics are typically made to resemble one interface in a protein-protein interaction (PPI), and thus perturb it. We recently proposed suitable chemotypes can be matched with interface regions directly, without regard for secondary structures. Here we describe a modular synthesis of a new chemotype 1, simulation of its solution-state conformational ensemble, and correlation of that with ideal secondary structures and real interface regions in PPIs. Scaffold 1 presents amino acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Many examples of the former approach have been reported using various nonamino acid units such as dibenzofurans, 6,7 oligoureas, 8−10 metallopeptides, 11−16 indolin-3-ones, 17 imidazolidin-2-ones, 18 epiindolines, 19 and oligothienylpyridines. 20 These mimics do not contain interstrand hydrogen bonding sites. Therefore, their general applicability to mimic protein−protein interactions via β-sheet formation is unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many examples of the former approach have been reported using various nonamino acid units such as dibenzofurans, 6,7 oligoureas, 8−10 metallopeptides, 11−16 indolin-3-ones, 17 imidazolidin-2-ones, 18 epiindolines, 19 and oligothienylpyridines. 20 These mimics do not contain interstrand hydrogen bonding sites. Therefore, their general applicability to mimic protein−protein interactions via β-sheet formation is unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Later they designed benzoylurea oligomers (3) as an alternative to oligophenylenes to mimic up to eight turns of an α-helix, and to solve synthesis as well as water solubility issues when extended scaffolds are needed. [64] Other groups have also developed efficient non-helical mimetics of biologically active α-helices, based on aromatic backbones (such as oligo-benzamides, [65] pyridazines, [66] -pyridyles [67] or -piperidine-piperidinones [68] ). Arora et al, on the other hand, have reported the oligooxopiperazine scaffold as chiral nonaromatic topographical helix mimetic.…”
Section: Helix Mimetics Based On Non-helical Scaffoldsmentioning
confidence: 99%
“…19,20 Other examples include peptides targeting HIV integrase, BCl-2 and β-catenin. [21][22][23] Apart from the stapling chemistry, some other motifs have been explored, including the β-strands mimetics 24 and loops motif 25 that display more complex topologies. Examples of tertiary mimetics as PPI inhibitors has also been reported, including α-and α/β-peptides derived from the "Z-domain" scaffold.…”
Section: Introductionmentioning
confidence: 99%